1997
DOI: 10.1539/joh.39.119
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Efficacy of a Few Diesters of Meso 2,3‐Dimercaptosuccinic Acid during Sub‐Chronic Arsenic Intoxication in Rats

Abstract: Therapeutic Efficacy of a Few Diesters of Meso 2,3-DimercaptosuccinicAcid during SubChronic Arsenic Intoxication in Rats: S.J.S. FLORA, et al. Division of Pharmacology and Toxicology, Defence Research and Development Establishment-The therapeutic efficacy of four diesters derivatives of meso 2,3-dimercaptosuccinic acid (DMSA) was investigated in subchronic arsenic intoxication in rats. Dimethyl DMSA (DMDMSA), diethyl DMSA (DEDMSA), diisopropyl DMSA (DiPDMSA) and diisoamyl DMSA (DiADMSA) were the diesters of DM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…Lead, in particular, can accumulate in the reproductive system and has been implicated in the development of oxidative stress via reactive oxygen species (ROS) and lipid peroxidation (Vaziri and Sica, 2004;Marchlewicz et al, 2004;Mishra and Acharya, 2004). In view of this, many investigators have used a variety of antioxidants and chelating agents for lead, including vitamin C (Hsu et al, 1998a;Saad and El-Sayed, 2014), vitamin E (Patra et al, 2011) and DMSA (Flora et al, 1997;Malvezzi et al, 2001) to prevent the occurrence and subdue oxidative stress in tissue. It has been reported that supplementation of vitamin E and/or C reduced sperm ROS generation, prevented loss of sperm motility and oocyte penetration capacity in lead-exposed rats (Hsu et al, 1998b;El-Neweshy and El-Sayed, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lead, in particular, can accumulate in the reproductive system and has been implicated in the development of oxidative stress via reactive oxygen species (ROS) and lipid peroxidation (Vaziri and Sica, 2004;Marchlewicz et al, 2004;Mishra and Acharya, 2004). In view of this, many investigators have used a variety of antioxidants and chelating agents for lead, including vitamin C (Hsu et al, 1998a;Saad and El-Sayed, 2014), vitamin E (Patra et al, 2011) and DMSA (Flora et al, 1997;Malvezzi et al, 2001) to prevent the occurrence and subdue oxidative stress in tissue. It has been reported that supplementation of vitamin E and/or C reduced sperm ROS generation, prevented loss of sperm motility and oocyte penetration capacity in lead-exposed rats (Hsu et al, 1998b;El-Neweshy and El-Sayed, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, vitamin C and vitamin E function together to protect membrane lipids from damage (Frei, 1991). Animal studies suggested that DMSA is an effective chelator of lead in soft tissues but it is unable to chelate lead from bone (Flora et al, 1997(Flora et al, , 2008. Vitamin C and/or vitamin E alone, or both in combination with conventional chelator was found to decrease lipid peroxide levels of soft organs (Patra et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, some monoesters and diesters of DMSA have been developed and tried as therapeutic agents for metal poisoning in mice and rats (Kostial et al, 1995;Xu et al, 1995;Blanusa et al, 1997;Flora et al, 1997;Pande et al, 2001). The efficiency increased with the number of carbon atoms in the alkyl group of the DMSA monoester and the best results were obtained with monoisoamyl DMSA (MiADMSA) (Kostial et al, 1994), which has the ability to gain intracellular access via a probenecidsensitive and sulphinpyrazone-sensitive transport mechanism(s) (Tasende et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…The efficacy of melatonin in cadmium induced cytotoxicity is mainly attributed to its high lipophilicity (Reiter, 2000). It is well documented that the lipophilic agents are found to be very effective in reducing toxic effects of heavy metals and their elimination from various organ systems (Flora et al, 1997;ElSokkary et al;2005). Due to its small size and lipophilicity, melatonin crosses biological membranes easily, thus reaching all compartments of the cell.…”
Section: Resultsmentioning
confidence: 99%